Traditional Cultural Learning System for Batak Toba Wedding Using Multimedia Approach - Samosir, Ridha Sefina; Adriel, Varian (Universitas Sanata Dharma, 2023)
Indonesia is a country with diverse cultures. Indonesia comprises numerous tribes include Batak Toba. The Batak Toba people actively practice their traditional rituals, including wedding ceremonies. Their traditional wedding ceremony involves several rituals, symbols, and attributes with different meanings. Moreover, the Batak Toba people spend considerable amounts of time on their traditional wedding ceremony. Today, learning resources for traditional rituals, attribute, and other can be accessed through experts’ knowledge, video tutorials, and scientific journal. However, all sources have failed to attract attention. Thus, only a few generations are concerned with and interested in studying culture. The research objective is to develop a system based on multimedia approach that provide learning materials about traditional rituals of Batak Toba wedding ceremony. The multimedia development life cycle method is used for system development. Furthermore, the conclusion of this research shows that multimedia such as images, audio, video, and animation can attract anyone to learn about cultural.